Peran Finansial Technology sebagai Katalisator Intensi Literasi Keuangan dan Inklusi Keuangan Pada Usaha Mikro Kecil dan Menengah (UMKM) di Jawa Tengah - Sochimin, Sochimin; Sabila, Sasti Amar (el-Jizya: Jurnal Ekonomi Islam, 2024)
As technology and information advances, new products and services often appear in society. The presence of financial technology (fintech) as a credible financial institution is one of the services that can provide solutions business financing problem that often arise in society, especially in Micro, Small, and Medium Enterprise (MSMEs) In Central Java. Central Java Province is on of the best provinces in Indonesia according to the financial services authority because it implements the MSME digitalization empowerment program. The aim of this scientific research is to analyze and understand the role of fintech in development of MSMEs in Central Java. A descriptive qualitative approach was used in this research. Secondary data was obtained from books and journals. Based on the findings of this research, financial institution such as fintech are commited to increasing access to financing for Cental Java MSMEs. This can be seen in increasing MSME credit, as well as reducing interest rate on MSMEs Credit, in order to encourage credit growth for regional economic recovery. Furthermore, financial literacy in Central Java is higher than the national financial literacy index, while financial inclusion in Central Java is lower than the national financial inclusion index. The Central Java Government hopes to meet the national target of 90% by 2024.